Study of Vitamin D Level in Paediatric Asthma at a Tertiary care Center - Kumar, Pankaj; Kumar, Rajesh; Singh, Pratap Bhanu (Journal of Nepal Paediatric Society, 2022)
Introduction: There are few studies that suggest low Vitamin D levels are associated with asthma. Present study was conducted to evaluate the association between vitamin D levels with asthma and its severity in children. Methods: This cross-sectional study included 70 children (35 asthmatic and 35 controls) aged between three to 12 yrs. CBC, AEC, IgE, spirometry, chest X-ray, and serum vitamin D levels were measured. Vitamin D levels were categorized according to guidelines of the American Academy of Paediatrics (2008) and compared between the two groups. The association between vitamin-D levels with asthma and its severity was studied. Results: The mean age of study group cases was 9.23 ± 2.62 yr. The male:female ratio in the study group was 2.5: 1. Cough and wheezing was the commonest manifestation (100%). Most of the patients had mild asthma (45.71%). Asthma was more common in the urban population (68.57%) and children belonging to lower socioeconomic status (51.43%). The markers of allergic disorders Eosinophils, AEC and IgE were elevated (all p-values ≤ 0.0001) in study group. Mean serum vitamin D levels in the study group and control group patients were 45.21 ± 28.52 nmol/L and 57.03 ± 40.01 nmol / L respectively. The mean levels of vitamin D in the study group were insufficient as per AAP criteria. Vitamin D levels were more deficient in severe asthma (26.19 ± 14.46 nmol/L). Conclusions: In the present study Vitamin D insufficiency was seen in patients with asthma.